Identification of a structural and functional domain in xNAP1 involved in protein–protein interactions - Friedeberg, Christine (Oxford University Press, 2006)
xNAP1 (Xenopus nucleosome assembly protein) belongs to the family of nucleosome assembly proteins (NAPs) and shares 92% identity with human and mouse NAP1. NAPs have been reported to have a role in nucleosome assembly, cell cycle regulation, cell proliferation and transcriptional control, although the precise function of NAP1 is still not clear. Here we report the identification of a putative domain of xNAP1 by limited proteolysis. This domain has been mapped in the xNAP1 protein sequence to residues 38–282 and thus lacks the acidic sequences at the N- and C-termini. We have studied this domain and related fragments in vitro and by a functional assay involving over-expression of the protein in Xenopus laevis embryos. Analytical ultracentrifugation shows that removal of the acidic N- and C-terminal regions does not prevent the formation of larger multimers, which are predominantly hexadecamers. Injection of mRNA encoding the full-length xNAP1 or the putative domain and other related constructs into Xenopus embryos gave identical phenotypes. These results are discussed in relation to protein–protein interactions between NAP1 octamers and a possible ‘squelching’ mechanism.